Piceid Octanoate Protects Retinal Cells against Oxidative Damage by Regulating the Sirtuin 1/Poly-ADP-Ribose Polymerase 1 Axis In Vitro and in rd10 Mice - Seyed Mohamadmehdi Moshtaghion; Estefanía Caballano-Infantes; Álvaro Plaza Reyes; Lourdes Valdés-Sánchez; Patricia Gallego Fernández; Berta de la Cerda; Maurizio S. Riga; Manuel Álvarez-Dolado; Pablo Peñalver; Juan C. Morales; Francisco J. Díaz-Corrales (MDPI AG, 2024)
Retinitis pigmentosa is a common cause of inherited blindness in adults, which in many cases is associated with an increase in the formation of reactive oxygen species (ROS) that induces DNA damage, triggering Poly-ADP-Ribose Polymerase 1 (PARP1) activation and leading to parthanatos-mediated cell death. Previous studies have shown that resveratrol (RSV) is a promising molecule that can mitigate PARP1 overactivity, but its low bioavailability is a limitation for medical use. This study examined the impact of a synthesized new acylated RSV prodrug, piceid octanoate (PIC-OCT), in the 661W cell line against H2O2 oxidative stress and in rd10 mice. PIC-OCT possesses a better ADME profile than RSV. In response to H2O2, 661W cells pretreated with PIC-OCT preserved cell viability in more than 38% of cells by significantly promoting SIRT1 nuclear translocation, preserving NAD+/NADH ratio, and suppressing intracellular ROS formation. These effects result from expressing antioxidant genes, maintaining mitochondrial function, reducing PARP1 nuclear expression, and preventing AIF nuclear translocation. In rd10 mice, PIC-OCT inhibited PAR-polymer formation, increased SIRT1 expression, significantly reduced TUNEL-positive cells in the retinal outer nuclear layer, preserved ERGs, and enhanced light chamber activity (all p values < 0.05). Our findings corroborate that PIC-OCT protects photoreceptors by modulating the SIRT1/PARP1 axis in models of retinal degeneration.